3-Aminobenzoic acid–4,4′-bipyridine (2/3) - Pornsuda Lhengwan (Acta Crystallographica Section E, 2012)
The asymmetric unit of the title compound, 3C10H8N2·2C7H7NO2, consists of three molecules of 4,4′-bipyridine (bpy) and two molecules of 3-aminobenzoic acid (bza). Two molecules of bza and two molecules of bpy are connected via O—H...N, N—H...N and N—H...O hydrogen bonds, forming forming infinite double-stranded zigzag chains along the c axis. The third molecule of bpy is linked to the chain by weak C—H...O interactions. Adjacent chains are linked via π–π interactions [centroid–centroid distances = 3.759 (3)–3.928 (3) Å] involving the pyridine rings of bpy molecules, resulting in a sheet-like structure parallel to (100). These sheets are stacked via C—H...π interactions, resulting finally in the formation of a three-dimensional supramolecular structure.